2021
DOI: 10.2147/vmrr.s289721
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Bovine Brucellosis in Ethiopia: Systematic Review and Meta-Analysis

Abstract: Brucellosis is an infectious and widespread zoonotic disease caused by bacteria of the genus Brucella and can induce considerable human suffering and huge economic losses in animals. Thus, the aim of this study was to conduct a systematic review and meta-analysis on the seroprevalence of bovine brucellosis in Ethiopia. PubMed, Science Direct, African Journals Online, and Google Scholar were used to search the articles. All references were screened and articles, which reported seroprevalence of bovine brucellos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
2
4
0
1
Order By: Relevance
“…In the present study, a strong association was observed between human brucellosis and handling of parturient materials, drinking raw milk, drinking raw milk from aborted animals, and drinking raw milk from cows with RFM, which is in agreement with studies conducted by [ 36 , 37 ]. The possible reason for this may be that in our study areas most of the participants drank raw milk, including raw milk from aborted and retained fetal membrane cows as it was assessed with interview questions.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, a strong association was observed between human brucellosis and handling of parturient materials, drinking raw milk, drinking raw milk from aborted animals, and drinking raw milk from cows with RFM, which is in agreement with studies conducted by [ 36 , 37 ]. The possible reason for this may be that in our study areas most of the participants drank raw milk, including raw milk from aborted and retained fetal membrane cows as it was assessed with interview questions.…”
Section: Discussionsupporting
confidence: 93%
“…The clinical manifestations pertaining to human brucellosis found in this study were similar to previous findings reported by [ 9 , 36 , 38 ]. Apart from general clinical manifestations, participants with a history of testicular swelling had a statistically significant association with Brucella seroprevalence.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Estudos em outros países também demonstram diferentes taxas de detecção, Marrocos 1,9% prevalência de brucelose e 9% tuberculose (Azami et al, 2018), África 8,68% brucelose e 6,86% para tuberculose (Chidumayo, 2021), Etiópia 3,0% brucelose (Tesfaye et al, 2021), Iran 7% para brucelose (Mirnejad et al, 2017) e China com soroprevalência geral de 1,9%, de 2008 a 2018 para brucelose em rebanhos leiteiros passando de 1,6% em 2008-2012 para 2,6% em 2013-2018 (Ran et al, 2019), sendo apontado pelos autores as principais causas para ocorrência das infecções, a não fiscalização de rebanhos, a movimentação de animais sem atestado sanitário, introdução de novos bovinos nas propriedades e sistemas de criação intensiva.…”
Section: Resultsunclassified
“…Bovine brucellosis is considered a widespread zoonosis by the World Health Organization and the Office International des Epizooties because it causes veterinary, public health and economic challenges in developing countries across the world (Tesfaye, 2021;Negash and Dubie, 2021;Lukambagire et al 2021). Bovine brucellosis causes substantial losses in dairy and beef cattle farms through reproductive inefficiencies and pregnancy loses.…”
Section: Introductionmentioning
confidence: 99%